Ionic Liquid (EmimAc)-Water Mixture Confined in Nanoporous Glass Matrices Studied With High-Resolution Neutron Spectroscopy - Frielinghaus, H.; Fomina, M.; Hayward, D.; Dubey, P. S.; Jaksch, S.; Falus, P.; Fouquet, P.; Fruhner, L.; Holderer, O. (Frontiers in Physics, 2022)
We report on the structure and diffusion behaviour of the various constituent molecules in ionic liquid (IL) mixtures under confinement in nanoporous glasses. X-Ray diffraction measurements indicate that the ions adopt a lamellar arrangement under confinement. Furthermore, using selective deuteration in combination with high resolution neutron spectroscopy reveals how the dynamics and the activation energy of the IL is affected by different confinement conditions (pore sizes 50 ˚A and 135 ˚A) and different temperatures (265 K and 318 K). With different deuteration schemes we could separate the different motions of acetate and water. The confinement leads to distortions of the domains, which gives more room for diffusion. In the smaller pores, the stronger distortion gives even more room such that the hydrogen bonds between acetate and water seem to be even stronger than in bulk and weaker confinement. The results are discussed in the context of previous measurements on dry samples.